2020
DOI: 10.3390/ijms21114071
|View full text |Cite
|
Sign up to set email alerts
|

Biological Factors behind Melanoma Response to Immune Checkpoint Inhibitors

Abstract: Modern immunotherapy together with targeted therapy has revolutionized the treatment of advanced melanoma. Inhibition of immune checkpoints significantly improved the median overall survival and gave hope to many melanoma patients. However, this treatment has three serious drawbacks: high cost, serious side effects, and an effectiveness limited only to approximately 50% of patients. Some patients do not derive any or short-term benefit from this treatment due to primary or secondary resistance. The response to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 121 publications
0
28
0
7
Order By: Relevance
“…Our results showed that the status of overall increased infiltrating immune cells in melanoma has the potential to predict clinical prognosis. Melanoma could be divided into ”hot” and “cold” status (enrich in or lack of immune cells infiltration), and the hot status is likely to correlate with antigen processing and higher expression of interferons, TNF and chemokines pathways ( 40 ). We further analyzed the infiltrating immune cell subtypes which correlated with the prognosis of melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that the status of overall increased infiltrating immune cells in melanoma has the potential to predict clinical prognosis. Melanoma could be divided into ”hot” and “cold” status (enrich in or lack of immune cells infiltration), and the hot status is likely to correlate with antigen processing and higher expression of interferons, TNF and chemokines pathways ( 40 ). We further analyzed the infiltrating immune cell subtypes which correlated with the prognosis of melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance, the number of Treg circulating in the blood of cancer patients and the infiltration of Treg into the tumor have been documented to be closely related to the progression and prognosis of multiple cancer entities [ 20 ]. More interestingly, the extent of Treg infiltration into human tumors has been proposed to show an inverse correlation with the response to ICI therapy [ 131 , 132 ]. Not least, this observation emphasizes the importance of Treg in the understanding of the anti-tumor immunity and thus the development of novel therapeutic approaches.…”
Section: Regulatory T Cellsmentioning
confidence: 99%
“…However, the efficacy of ICI therapy varies greatly from patient to patient. [ 22 ] Although previous studies have shown that patients with high PD-L1, high tumor mutation burden and DNA mismatch-repair deficient/microsatellite instability-high can benefit more from ICI therapy, [ 22 24 ] we need to further explore the clinical factors affecting the therapeutic effect. Therefore, we started from BMI to reveal its impact on ICI therapy and the prognosis of advanced LSCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…[ 22 ] Recent studies had shown that ICI therapy is more effective in tumor patients with high PD-L1 expression, high tumor mutation burden, and DNA mismatch-repair deficient /microsatellite instability-high. [ 22 24 ] Therefore, to find out the factors that affect the effect of ICI therapy can not only guide the choice of clinical treatment, but also explore the new direction of scientific research. Therefore, the purpose of this study is to explore the effect of pretreatment BMI on the prognosis and serum immune cells in the advanced LSCC patients who received ICI therapy.…”
Section: Introductionmentioning
confidence: 99%